Regulatory considerations for paediatric drug evaluation in China. Issue 1 (2nd May 2023) - Geng, Ying; Li, Qiang; Sun, Yan-Zhe; Zhang, Hao; Jiang, Yong-Lin; Wang, Li-Qing; Wu, Yue-E; Zhao, Wei; Yang, Zhi-Min
Abstract : The regulatory guidelines for the research and development of paediatric drugs are still evolving in China. The formulation of the guidelines started from learning and borrowing existing experience, and gradually changed to the exploration and improvement of local guidelines, which was not only in line with international standards but also had breakthroughs, innovations and Chinese characteristics. In this paper, the current setting of paediatric drug research and development in China and corresponding technical guidelines have been introduced from regulatory perspectives, and the accessibility of further improvement in regulatory strategies has also been discussed.